Wheat Rhizosphere Microbiota Respond to Changes in Plant Genotype, Chemical Inputs, and Plant Phenotypic Plasticity - Jacquiod, Samuel; Raynaud, Tiffany; Pimet, Eric; Ducourtieux, Chantal; Casieri, Leonardo; Wipf, Daniel; Blouin, Manuel (Frontiers in Ecology and Evolution, 2022)
Modern wheat varieties that were selected since the Green Revolution are generally grown with synthetic chemical inputs, and ancient varieties released before1960 without. Thus, when changes occur in rhizosphere microbiota structure, it is not possible to distinguish if they are due to (i) changes in wheat genotypes by breeding, (ii) modifications of the environment via synthetic chemical inputs, or (iii) phenotypic plasticity, the interaction between wheat genotype and the environment. Using a crossed factorial design in the field, we evaluated the effects of either modern or ancient wheat varieties grown with or without chemical inputs (a N fertilizer, a fungicide, and an herbicide) on “microbiome as a phenotype.” We analyzed the rhizosphere microbiota by bacterial and fungal amplicon sequencing, coupled with microscope observations of mycorrhizal associations. We found that plant genotype and phenotypic plasticity had the most influence on rhizosphere microbiota, whereas inputs had only marginal effects. Phenotypic plasticity was particularly important in explaining diversity variations in bacteria and fungi but had no impact on the mycorrhizal association. Our results show an interest in considering the interaction between wheat genotype and the environment in breeding programs, by focusing on genes involved in the phenotypic plasticity of plant-microbe interactions.